2014
DOI: 10.16970/ted.67061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave radiation on stored product pest Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) larvae

Abstract: This study was designed to examine the effects of microwave radiation exposure on Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae) larvae. One to two day old larvae were exposed to microwave radiation at the powers of 70, 150, 300 and 600 W for different exposure times (1-50 s). Mortality ratio in larvae increased significantly with increasing exposure time at all powers of microwave radiation. Completele mortality was achieved at the power of 70 W and the longest exposure time (50 s) Superoxide dismutase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Larval and pupal mortality significantly increased on all given treatments of UV-B light as contrast to control group. Same outcome also was found by (Faruki et al, 2005;Pandir and Guven, 2014;Guven et al, 2015;Ali et al, 2016) they reported that larval and pupal mortality was totally related with irradiation doses. Insects mortality ratio enhance with rising UV-B light time.…”
Section: Resultssupporting
confidence: 77%
“…Larval and pupal mortality significantly increased on all given treatments of UV-B light as contrast to control group. Same outcome also was found by (Faruki et al, 2005;Pandir and Guven, 2014;Guven et al, 2015;Ali et al, 2016) they reported that larval and pupal mortality was totally related with irradiation doses. Insects mortality ratio enhance with rising UV-B light time.…”
Section: Resultssupporting
confidence: 77%
“…Some studies used small mammalian species, living in or close to polluted areas for detection of hazardous pollution (Farbairn et al, 1995;Petras et al, 1995;Tice, 1995;Baker et al, 1996;Salagovic et al, 1996;Ralph et al, 1997;Silva et al, 2000). Also, comet assay has been applied to cells of insects, including Shistocerca gregaria, Drosophila melanogaster, Curculio sikkimensis, mosquito larvae, Ephestia kuehniella and in grasshoppers Chorthippus brunneus (Siddique et al, 2005;Todoriki et al, 2006;Augustyniak et al, 2006;Yousef et al;, Abdel-Gawad et al, 2011Isabel and Maria, 2014;Pandir and Guven, 2014).…”
mentioning
confidence: 99%
“…However, exposure of Ephestia kuehniella Zeller larvae to microwave radiation at power of 70W for 50 sec. resulted in a complete mortality (Pandir and Guven, 2014). Moreover, Al-Akhdar et al (2019) recorded complete reduction in R. dominica adults after microwave exposure at medium power for 4 min.…”
Section: Effect Of Microwave Radiation On R Dominica Adultsmentioning
confidence: 97%